The Relationship Between Body Mass Index and Muscle Strength in FK Unjani Students Class Of 2023 - Apen Afgani Ridwan; Hedi Hendrawan Rachmatdinata; Ilham Faruq Saputra (Sean Institute, 2025)
Body mass index (BMI) is an indicator of nutritional status that affects health and muscle strength. Obesity inhibits AMPK, which can reduce endurance and decrease muscle function, increasing the risk of disease. This study aims to determine the relationship between BMI and muscle strength in students at the Faculty of Medicine, Jenderal Achmad Yani University. This research used a cross-sectional analytical observational study method on pre-clinical students at the Faculty of Medicine, Jenderal Achmad Yani University Class of 2023. Samples were taken using inclusion and exclusion criteria, involving measurements of body mass index, grip strength, and jumps. Data analysis uses SPSS and complies with research ethics. The research results show that the majority of FK Unjani Class of 2023 students have a normal body mass index (BMI) (50%), which indicates good nutritional status. All respondents with overweight and obese BMI classes I and II showed standing long jump results below average (100%); only 7.1% of respondents with normal BMI reached the average category. Most respondents with normal BMI had normal hand strength (57.1%), as did those with class II obesity (83.3%). There was no significant relationship between BMI and muscle strength after being tested using the chi-square statistical test, with p-values of 0.629 and 0.792, respectively. This research is in line with previous studies that showed insignificance in the relationship between BMI and muscle strength. The majority of FK Unjani Class of 2023 students have normal BMI, normal muscle strength in handgrip strength, and low in standing long jump. There is no significant relationship between BMI and muscle strength.